Fighting monsters through the vulnerable hero: an examination of techniques of role play within drama therapy for children who have experienced trauma in South Africa. - Hutton, Emma (My University, 2019)
My interest in this research was sparked by own my experiences as a child. I would take on heroic characters from movies, literature and of my own invention in order to cope with painful medical procedures. Through them I was able to find strength in these moments as well as in my later life. It also helped me to process my feelings of abandonment in these moments. I believe that embodying these characters also gave me a strong sense of moral conviction that continues to this day. I believe that this has been a large part of what has led me to the work I am embarking on today as I have a strong sense of wanting to help others, especially children. I have a strong sense of wanting to be part of creating a positive change in the world and to stand against what I perceive to be injustice. As part of my master’s programme I created and performed a performance as research (PAR) project that investigated the impact this kind of role play had and continues to have on me. My findings were that taking on these roles were extremely helpful to me in that allowed me to find a sense of inner strength that helped me to cope with difficult circumstances and continues to help me today. However, it has also left me dissociated from my perceived weaknesses and vulnerabilities, feeling like I always have to take on the roles of perceived strength. This have impacted on my emotional health as it is difficult for to express and process feelings I consider “weak” and on my ability to form meaningful intimate relationships with others. Therefore, I feel there is need for greater flexibility and integration within this role. This has partly informed this research as the data I gathered in my PAR has been part of developing my assumptions for this research. I am investigating whether this kind of role play could be useful to other children in the ways that it was to me as well as how one might work towards finding greater integration and integration within the role of the hero.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Drama Therapy to the Humanities, University of the Witwatersrand, Johannesburg,